Coagulation Activation Following Estrogen Administration to Postmenopausal Women - Caine, Yehezkel G; Bauer, Kenneth A; Barzegar, Samad; ten Cate, Hugo; Sacks, Frank M; Walsh, Brian W; Schiff, Isaac; Rosenberg, Robert D (Thrombosis and Haemostasis, 1992)
We investigated coagulation system activation following estrogen treatment in 29 healthy postmenopausal women. Study participants received conjugated estrogens at 0.625 and 1.25 mg per day, and placebo for 3-month periods in a randomized crossover protocol. Blood samples were obtained on two consecutive days at the end of each treatment period for immunoassays of F1+2 and fibrinopeptide A (FPA), markers of factor Xa action on prothrombin and thrombin action on fibrinogen in vivo, respectively. Treatment with estrogens at a dose of 0.625 or 1.25 mg resulted in significant increases in mean F1+2 levels of 40 and 98%, respectively, and in mean FPA levels of 37 and 71%, respectively. The measurements of F1+2 were significantly higher in women receiving 1.25 mg of estrogen than 0.625 mg. We also observed significant declines in the levels of antithrombin III and total protein S antigen. Immunologic levels of protein C increased modestly at only the 1.25 mg estrogen dose level. These data indicate that low doses of oral estrogens (≤1.25 mg per day) frequently increase the amount of thrombin generated in vivo. Our observations may help to explain the increased thrombotic risk that has been observed with higher doses of this medication (≥2.5 mg).